Immune boosting by B.1.1.529 (Omicron) depends on previous SARS-CoV-2 exposure - Reynolds,CJ; Pade,C; Gibbons,JM; Otter,AD; Lin,K-M; Sandoval,DM; Pieper,FP; Butler,DK; Liu,S; Joy,G; Forooghi,N; Treibel,TA; et al. (Science, 2022)
INTRODUCTIONB.1.1.529 (Omicron) and its subvariants pose new challenges for control of the COVID-19 pandemic. Although vaccinated populations are relatively protected from severe disease and death, countries with high vaccine uptake are experiencing substantial caseloads with breakthrough infection and frequent reinfection.RATIONALEWe analyzed cross-protective immunity against B.1.1.529 (Omicron) in triple-vaccinated health care workers (HCWs) with different immune-imprinted histories of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection during the ancestral Wuhan Hu-1, B.1.1.7 (Alpha), and B.1.617.2 (Delta) waves and after infection during the B.1.1.529 (Omicron) wave in previously infection-naïve individuals and those with hybrid immunity, to investigate whether B.1.1.529 (Omicron) infection could further boost adaptive immunity. Spike subunit 1 (S1) receptor binding domain (RBD) and whole spike binding, live virus neutralizing antibody (nAb) potency, memory B cell (MBC) frequency, and T cell responses against peptide pools and naturally processed antigen were assessed.RESULTSB and T cell recognition and nAb potency were boosted against previous variants of concern (VOCs) in triple-vaccinated HCWs, but this enhanced immunity was attenuated against B.1.1.529 (Omicron) itself. Furthermore, immune imprinting after B.1.1.7 (Alpha) infection resulted in reduced durability of antibody binding against B.1.1.529 (Omicron), and S1 RBD and whole spike VOC binding correlated poorly with live virus nAb potency. Half of triple-vaccinated HCWs showed no T cell response to B.1.1.529 (Omicron) S1 processed antigen, and all showed reduced responses to the B.1.1.529 (Omicron) peptide pool, irrespective of SARS-CoV-2 infection history. Mapping T cell immunity in class II human leukocyte antigen transgenics showed that individual spike mutations could result in loss or gain of T cell epitope recognition, with changes to T cell effector and regulatory programs